Study of the relationship between job stress and intention to leave the nursing profession - Darvish, Hassan; Shabani, Fatemeh (Advances in Nursing & Midwifery, 2013)
Abstract: Background: Nowadays, Neglect of nursing problems in the world, including stress has created many problems and these problems have caused that nurses tend to leave jobs or even leave their job. This study is designed to find the relationship between job stress and intention to leave the profession in nurses in public and private hospitals in Shiraz in 1390 . Materials and Methods: This study is a descriptive-correlational research. Using stratified sampling and Morgan’s formula, nurses from government hospitals, nurses from private hospitals were selected. Tools of collecting data included demographic questionnaire and scales of occupational stress and questionnaire for tending leaving job. Data were analyzed using simultaneous multiple regression analysis, Pearson, Friedman and T test. Results: Results showed that there is a statistically significant relationship between job stress and intention to leave the job of public and private hospitals with a correlation coefficient of , and tending to leaving job is expected by job stress and its components. Stress job and tending to leaving job in female nurses than male nurses is much higher (p= ), while there is no statistically significant difference between job stress and intention to leave job in private hospitals and public hospitals. Conclusion: Organizations so that they can understand the reasons and factors contributing to employee turnover, using the right information and Timely forecasts, can be used to effectively manage the process of maintaining an efficient workforce. Also, managers can to increase efficiency and productivity in the organization with the best possible way using identification of stressors and put under the control of them. Keywords: Tension, stress, leaving job, nurses, public and private hospitals, Shiraz